The most valuable player may not be on the winning team: Uncovering consumer tolerance for color shades in roses. (January 2016) - Grygorczyk, A.; Mhlanga, S.; Lesschaeve, I.
Highlights: Examined consumer preferences for rose colors. Consumer tolerance to shade variations differs across color categories. Some color categories are riskier pursuits than others. Abstract: Color is often found to be the most important factor driving consumer purchase decisions for flowers. However due to the sheer number of flower color options available, pinpointing which flower shades to aim for in a breeding program is a complex task. Discussions with local growers revealed discrepancies between color preferences previously identified and actual consumer demand. The present work examines this in further detail by applying two methods of testing consumer flower color preference with the same panel of consumers: conjoint analysis using color categories and a follow-up question asking consumers to pick their 3 most preferred colors from a chart of 60 colors. Consumers were found to have different tolerance ranges for shades across color categories. Consumers have a wide range of tolerance for red colors, making this a safe target as nearly all shades of red tested were well liked by consumers. By contrast, in the yellow category there was one very high performing shade, with consumer preference dropping off sharply with any deviation from this shade. While this particular shade of yellow could potentially be highly successful with consumers, it is a riskier target as breeders would have a narrow range of tolerance in shade variation to achieve consumer success. This study presents a new understanding of consumer preference as it suggests that consumers exhibit not only preference intensity for sensory stimuli, but also a tolerance range for variations on the stimulus. Interestingly, tolerance ranges are not consistent across categories of sensory stimuli (e.g. color categories).